2011
DOI: 10.1080/14790718.2011.606908
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic and cultural authenticity of ‘Spanglish’ greeting cards

Abstract: Past scholarly work has examined commercial greeting cards as an important cultural practice. The growing presence in the USA of bilingual greeting cards offers a site for understanding public uses of contact varieties of language. This paper analyses the reactions of 30 college educated US-raised bilingual Latinos to 17 intrasententially codeswitched SpanishÁEnglish greeting cards. Despite a few exceptions, there were correlations between the felicitousness of the codeswitches and their acceptability ratings.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…On the other hand, comprehension may not play a part at all for consumers with low English proficiency, in that for them English only has symbolic value (e.g., Haarmann 1989;Ray, Ryder, and Scott 1991;Piller 2003Piller , 2001Kelly-Holmes 2005;Kuppens 2010). For this group of consumers, the actual meaning of the English texts in ads may be less important than the values that English stands for, such as, sophistication or modernity (Kelly-Holmes 2000, 67;Piller 2003, 175;Kuppens 2010, 116-17;Tufi and Blackwood 2010;Potowski 2011;Taylor-Leech 2012;Manan et al 2015;Santello 2015, 4).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, comprehension may not play a part at all for consumers with low English proficiency, in that for them English only has symbolic value (e.g., Haarmann 1989;Ray, Ryder, and Scott 1991;Piller 2003Piller , 2001Kelly-Holmes 2005;Kuppens 2010). For this group of consumers, the actual meaning of the English texts in ads may be less important than the values that English stands for, such as, sophistication or modernity (Kelly-Holmes 2000, 67;Piller 2003, 175;Kuppens 2010, 116-17;Tufi and Blackwood 2010;Potowski 2011;Taylor-Leech 2012;Manan et al 2015;Santello 2015, 4).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This recognition is thought to evoke stereotypes about English, which are subsequently transferred to the product advertised. Stereotypical associations evoked by English include notions such as modernity, prestige, international orientation, and sophistication (Kelly-Holmes 2000, 67;Piller 2003, 175;Kuppens 2010, 116-117;Tufi and Blackwood 2010;Potowski 2011;Taylor-Leech 2012;Santello 2015, 4;Manan et al 2015). Kuppens (2010, 116) observes that advertisements sometimes contain "meaningless words or sentences that only sound English, " illustrating that what matters is not the meaning of the foreign language used in the ad, but the image conjured up by the foreign language.…”
mentioning
confidence: 99%
“…3 (Hill 2008, 156-157) Hill's (1995aHill's ( , 1995bHill's ( , 1998 work on Mock Spanish is seminal. Others who have treated the subject include Barrett (2006), Breidenbach (2006), Callahan (2010), Mendoza-Denton (2008), Potowski (2011), Schwartz (2006, and Zentella (2003). Barrett (2006) analyzes the use of Mock Spanish by non-Latino restaurant workers to address Spanish monolingual co-workers; Zentella (2003) describes U.S. Latinos' linguistic virtuosity and how it defies the pejorative image of Hispanics that Mock Spanish indexes.…”
Section: Introductionmentioning
confidence: 98%
“…Breidenbach's (2006) study incorporates psycholinguistic experiments to discover whether exposure to Mock Spanish facilitates belief in negative stereotypes of Hispanics. Potowski (2011) tested acceptance of greeting cards featuring Spanish and English, finding that the ones her participants rejected contain usages characteristic of Mock Spanish. Mendoza-Denton (2008) reports that exaggeratedly anglicized pronunciations -in the style of the examples given at the beginning of this paper -were judged highly offensive by her Chicana consultants.…”
Section: Introductionmentioning
confidence: 99%
“…Our respondents included people of Christian (15), Atheist (14), Agnostic (4), Muslim (1), Sikh (1), Hindi (1) and Not Listed (11) faith. We found that religion was not a determinant of whether or not participants sent cards; religious affiliation did not appear to impact sending behaviour.…”
Section: Methodsmentioning
confidence: 99%